FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH DALAM MENABUNG DI BANK SYARIAH - RONI ANDESPA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2017)
The research theme is the financial and banking institutions. The study was conducted in West Sumatra. The research objective is: to look at the factors that affect the interest of the customer to save money in Islamic banks. Research using factor analysis. Samples used in this study are as many as 250 customers. Results of the study are: There are 4 factors that consist of 16 variables that have a value above 0.5, namely: Factor 1 (Age and Lifecycle, Beliefs and Attitudes, Motivation, Personality and Self-Concept, Lifestyle and Learning). Factor 2 (Perception, Reference Group, Social Class, Role and Status). Factor 3 (Product, Price, Promotion and Place). Factor 4 (Culture and Family).